Data Rights Law 3. 0 : The Legislative Prospect. - Lian, Yuming. (Peter Lang Ltd. International Academic Publishers, 2021)
This book discusses that to be among the world's leading digital economies, China needs to promote higher quality, fairer and more sustainable institutional protection for data rights and subject-relevant interests, and the ability to offer systematic and accurate legal rules within the various digital disciplines.